Public Speaking Melalui Diplomasi Kesantunan Berbahasa Di Balatkop Pemprov Jawa Barat - Amalia, Rosaria Mita; Citraresmana, Elvi; Saefullah, Nurul Hikmayaty (Universitas Nusantara PGRI Kediri, 2019)
Many cooperation partners of the provincial government of West Java come from other countries that have different cultures with Indonesian or Sundanese. Language skills in the sphere of diplomacy associated with language politeness are needed here in order to make the goal of negotiation achieved and provide benefits to the people of West Java. Community Service Activities is conducted in public speaking training activities. This research uses a pragmatic approach. The theories used are a Pragmatic theory by Levinson (1983) and Speech situation theory by Leech (1993). This research applies a qualitative descriptive method in the social field especially language, communication, and international relations. The purpose of this activity is to provide knowledge and insight for the staff of the Bureau of Domestic and International Cooperation in West Java and also to improve their communication ability. The implementation of this activity received a positive response from the participants. They feel that this activity is very useful and provide insight and skills to speak more in public. This is very crucial for the lecturer and business agent in the Agency for Cooperatives and Entrepreneurship Training (Balatkop) of West Java Province. In addition, the benefit of conducting this Community Service Activity is useful scientific empowerment for the community as well as the existence of article regarding this activity thus it becomes more extensive.